Revisiting correlates of sociosexuality for men and women: The role of love relationships and psychological maladjustment - Felix Neto (2015)
The purpose of this work was to examine the links between sociosexuality, and love relationships and psychological maladjustment. Although males and females vary in connection with the sociocultural orientations, the involvements of this variation may not be similar for both sexes. The sample included 475 participants, 42% women and 58% men. Ages ranged from 18 through 80 (M = 37.28, SD = 16.27). Measures assessed sociosexuality, love styles, love satisfaction, compassionate love, commitment, romantic loneliness, and negative affect. Men displayed a more unrestricted sociosexual orientation than women. We found both sex similarities and differences in the associations between sociosexuality and love relationships and psychological maladjustment. For both sexes a similar pattern of correlations was found regarding erotic love, love satisfaction, and commitment. It seems that unrestricted women experience more psychological maladjustment, evidenced by romantic loneliness and negative affect than men. The findings are discussed with reference to past research and some suggestions for further work are also noted.